2019
DOI: 10.33470/2379-9536.1228
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Long Acting Reversible Contraceptives for Adolescents in Urban vs Rural West Virginia Counties

Abstract: The study objective was to evaluate long acting reversible contraceptive (LARC) method availability and access for adolescents in rural and urban counties in West Virginia (WV). A cross-sectional survey of Title X family planning providers throughout WV was conducted from January 2016 to July 2017. This survey was sent to 226 family planning providers in WV to assess patterns of LARC availability. The survey assessed provider training level, LARC services provided and frequency, clinical practice, referral pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Insurance coverage is important for enabling access to effective contraception and contributes to positive health outcomes. 7 , 17 19 While not independently associated with adolescent births, HPSA designation was also more common among Appalachian counties. Taken collectively, these findings underscore the potential impact of structural, financial, and geographic barriers to accessing providers and contraceptive services among vulnerable populations, such as the Appalachian region.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Insurance coverage is important for enabling access to effective contraception and contributes to positive health outcomes. 7 , 17 19 While not independently associated with adolescent births, HPSA designation was also more common among Appalachian counties. Taken collectively, these findings underscore the potential impact of structural, financial, and geographic barriers to accessing providers and contraceptive services among vulnerable populations, such as the Appalachian region.…”
Section: Discussionmentioning
confidence: 84%
“…Taken collectively, these findings underscore the potential impact of structural, financial, and geographic barriers to accessing providers and contraceptive services among vulnerable populations, such as the Appalachian region. 17 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 Previous studies have demonstrated that the rural adolescent population in West Virginia has low reproductive health knowledge, 13,14 and may face unique obstacles to contraception access. 15 Barriers to rural adolescents include distance to healthcare providers, limited access to certain contraceptives such as intrauterine devices and implants, and variability of sex education curriculum presented at school. 13,15 Therefore, a technology-based sexual health tool that is tailored to this population to provide education and local resources, could have a significant impact on adolescent risk reduction.…”
Section: Introductionmentioning
confidence: 99%
“…15 Barriers to rural adolescents include distance to healthcare providers, limited access to certain contraceptives such as intrauterine devices and implants, and variability of sex education curriculum presented at school. 13,15 Therefore, a technology-based sexual health tool that is tailored to this population to provide education and local resources, could have a significant impact on adolescent risk reduction. In order to develop a tool for this demographic, a pilot study was necessary among populations that could give feedback as to the acceptability, feasibility, and accuracy of the website prior to distribution among rural adolescents.…”
Section: Introductionmentioning
confidence: 99%